Siem: Santiago (Chile) Integrated Energy Model [Mies: Modelo Integrado de Energía Para Santiago, Chile] - Carbonnel-Torralbo, A; Martin-Quijada, R (Pontificia Universidad Catolica de Chile, Escuela de Construccion Civil, 2019)
This paper presents a framework for the "Santiago Integrated Energy Model" or SIEM. This model establishes an optimized energy balance between the photovoltaic generation potential and the electric consumption curves of a specific Urban Energy District (EUD), designed for the city of Santiago. To validate local data, a methodology has been developed in three stages: the potential prospection and the curves estimation; the data calibration; and the EUD identification. The model has been applied in an hypothetical urban area to develop a consistency test, obtaining adequate results on the balance curves of the model, considering both the potential generation and consumption (according to uses and schedules). The results reflect the relevance of applying this model to a real urban area in Santiago of Chile, to establish optimization correlations for an empirical validation. © 2017.; Este artículo presenta un marco de desarrollo para el "Modelo integrado de energía para Santiago" o MIES. El modelo propone optimizar un balance energético entre el potencial de generación fotovoltaico y las curvas de consumo eléctricas de un determinado Distrito de Energía Urbano (DEU) para la ciudad de Santiago. Para validar datos locales, se desarrolla una metodología en tres etapas: la prospección del potencial de generación y la estimación de curvas de consumo eléctrico; la calibración de datos; y la identificación de un DEU. El modelo ha sido aplicado en un área hipotética urbana para desarrollar una prueba de concepto, obteniendo resultados adecuados sobre las curvas de balance del modelo, considerando tanto potencial de generación como consumo (según actividades y horarios). Los resultados sugieren la importancia de aplicar este modelo en un área urbana real en Santiago de Chile, para establecer una validación empírica mediante correlaciones de optimización. © 2017.